Matematyka
kuba96212
2017-06-24 12:41:55
Rozwiąż i sprawdź następujące układy równań: 3(x-1) + 2(2-y) = -5 - y 2x + 3y = 7
Odpowiedź
hiddendreams
2017-06-24 16:06:15

3x-3+4-2y=-5-y 2x+3y=7 3x-y=-6 2x+3y=7 9x-3y= -18 2x+3y=7 11x=-11 x= -1 -2+3y=7 3y=9 y=3 sprawdzenie: 2*(-1)+3*3=7 9-2=7 7=7 L=P

Konto usunięte
2017-06-24 16:07:30

3(x -1) + 2(2 - y) = -5 - y 2x + 3y = 7 3x - 3 + 4 - 2y = -5 - y 2x + 3y = 7 3x - y = -6     |·3 2x + 3y = 7 9x - 3y = -18 2x + 3y = 7 -------------------    +    (dodajemy stronami) 11x = -11     /:11 x = -1 y = 3x + 6 y = 3·(-1) + 6 y = 3 {x = -1 {y = 3 Sprawdzenie: 1° L = 9·(-1) - 3·3 = -9 - 9 = -18 P = - 18 L = P 2° L = 2·(-1) + 3·3 = -2 + 9 = 7 P = 7 L = P

Dodaj swoją odpowiedź